The Interplay Between Food Allergy and Atopic Dermatitis: Mechanism, Diagnosis, and Management - Ike Martyani; Cut Putri Hazlianda (GLOBAL HEALTH SCIENCE GROUP, 2026)
Atopic dermatitis (AD) and food allergy (FA) are two conditions that frequently coexist and present significant challenges in both diagnosis and management. This review aims to describe the link between atopic dermatitis and food allergy, as well as their diagnosis, management, and prevention, especially in the Asian context. The findings indicate that impairment of the skin barrier and exposure to food allergens through the skin (epicutaneous sensitization) play central roles in the development of FA among individuals with AD. From a diagnostic perspective, it is essential to distinguish between food sensitization and clinically significant food allergy in order to avoid unnecessary elimination diets. Management strategies encompass comprehensive care for AD, including skin-barrier maintenance and anti-inflammatory therapy, alongside evaluation for FA when clinically indicated, and avoidance of confirmed trigger foods. Preventive efforts, particularly in high-risk infants, show promise through early skin-barrier care and controlled introduction of food allergens. In the Indonesian and broader Asian contexts, adaptation of these strategies should consider local dietary patterns and the availability of allergy and dermatology services.